Spatio-temporal growth of a traditional urban centre in Nigeria - Mukhtar Olayiwola, Adewale; Olorunwa Salau, Wakeel (Spatial information research (Online), 2023)
This study analysed the spatio-temporal land use and land cover (LULC) changes in Ijebu Ode, Nigeria; determined the changes in the urban land use between 1986 and 2021; and predicted the future LULC changes in the study area. The study used data obtained through Global Positioning System (GPS) receiver and satellite imageries of 1986, 2000, 2014 and 2021. Data were analysed using digital image processing change detection techniques and CA-Markov analysis using TerrSet Geospatial Modelling and Monitoring System, version 19.0 and ArcMap 10.8.1 software. Results indicated that the built-up area of Ijebu Ode expanded from 9.073 km 2 in 1986 to 36.43 km 2 in 2021 due to reduction in bare land, cultivated area and vegetation. Results of transition probability indicated that while vegetation and built-up areas incessantly increasing, bare land and cultivated land were characterised with continual dynamisms. Result of land use simulation showed that by 2060 the built-up area would have increased to 47.32 km 2 . The study noted a situation of land use invasion and succession through transition of other land uses to built-up. The study concluded that the expansion of the built-up area is a signal towards urban sprawl in the study area. Hence, the study recommended that for a constant checking and evaluation of physical planning implication of land uses.